Toronto Notes 2022 : Comprehensive Medical Reference and a Review for the Medical Council of Canada Qualifying Exam (MCCQE) / Yuliya Lytvyn, Maleeha A. Qazi - Lytvyn, Yuliya
The 2022 edition features content updates across the main text, figures, graphics, and evidence-based medicine sections that are consistent with the most recent MCCQE objectives. Many landmark trials have been included to reflect the most current evidence across all medical specialties. The new division of Toronto Notes into three textbooks—medicine, surgery, and primary medicine—enhances readability and eases the load of studying for the Canadian and American medical licensing exams. We have also redesigned our website to more closely reflect the layout of the textbook and to enrich the learning experience.